Subcutaneous Adipose Tissue Macrophage Infiltration Is Associated With Hepatic and Visceral Fat Deposition, Hyperinsulinemia, and Stimulation of NF-κB Stress Pathway - Lê, Kim-Anne; Mahurkar, Swapna; Alderete, Tanya L.; Hasson, Rebecca E.; Adam, Tanja C.; Kim, Joon Sung; Beale, Elizabeth; Xie, Chen; Greenberg, Andrew S.; Allayee, Hooman; Goran, Michael I. (Diabetes (New York, N.Y.), 2011)
To examine in obese young adults the influence of ethnicity and subcutaneous adipose tissue (SAT) inflammation on hepatic fat fraction (HFF), visceral adipose tissue (VAT) deposition, insulin sensitivity (SI), β-cell function, and SAT gene expression. SAT biopsies were obtained from 36 obese young adults (20 Hispanics, 16 African Americans) to measure crown-like structures (CLS), reflecting SAT inflammation. SAT, VAT, and HFF were measured by magnetic resonance imaging, and SI and β-cell function (disposition index [DI]) were measured by intravenous glucose tolerance test. SAT gene expression was assessed using Illumina microarrays. Participants with CLS in SAT (n = 16) were similar to those without CLS in terms of ethnicity, sex, and total body fat. Individuals with CLS had greater VAT (3.7 ± 1.3 vs. 2.6 ± 1.6 L; P = 0.04), HFF (9.9 ± 7.3 vs. 5.8 ± 4.4%; P = 0.03), tumor necrosis factor-α (20.8 ± 4.8 vs. 16.2 ± 5.8 pg/mL; P = 0.01), fasting insulin (20.9 ± 10.6 vs. 9.7 ± 6.6 mU/mL; P < 0.001) and glucose (94.4 ± 9.3 vs. 86.8 ± 5.3 mg/dL; P = 0.005), and lower DI (1,559 ± 984 vs. 2,024 ± 829 × 10(-4) min(-1); P = 0.03). Individuals with CLS in SAT exhibited upregulation of matrix metalloproteinase-9 and monocyte antigen CD14 genes, as well as several other genes belonging to the nuclear factor-κB (NF-κB) stress pathway. Adipose tissue inflammation was equally distributed between sexes and ethnicities. It was associated with partitioning of fat toward VAT and the liver and altered β-cell function, independent of total adiposity. Several genes belonging to the NF-κB stress pathway were upregulated, suggesting stimulation of proinflammatory mediators.